Editorial note - Petryk, H. (Archives of Mechanics, 2020)
The following article ARCHIVES OF MECHANICS Arch. Mech. 71 (2), 155–171, 2019, DOI: 10.24423/aom.3057 Influence of initial density of granular stack on transient regime of homogeneous fluidization A.S. DRAME, L. WANG, B. DIOURTE has been withdrawn.